THE EFFECT OF LEADERSHIP STYLE, MOTIVATION, REWARD AND PUNISHMENT ON LOYALTY WITH JOB SATISFACTION AS INTERVENING VARIABLE ON EMPLOYEES OF PT. TELEKOMUNIKASI SELULAR SUMATRA, CENTRAL PART - Suherti, Suherti; Indrayani, Indrayani; Khaddafi, Muammar; Titik Windayati, Diana (RADJA PUBLIKA, 2022)
The purpose of this study is to analyze the influence of leadership style, motivation, reward and punishment on loyalty, analyze the influence of leadership style, motivation, reward and punishment, and job satisfaction on loyalty, analyze the direct and indirect effects of leadership style, motivation, reward and punishment simultaneously. and partially have a significant effect on loyalty with job satisfaction. The population in this study were 163 employees of PT. Central Sumatra Cellular Telecommunications. In this study, the sampling technique used is non-probability sampling with the technique taken is saturated sampling (census). The data collection technique in this research is to provide or distribute a list of questions or what is called a questionnaire. The sampling method used in this study is a non-probability method. The results showed that leadership style, motivation, reward and punishment had a significant effect on loyalty, and the results showed that leadership style, motivation, reward and punishment, and job satisfaction had a significant effect on loyalty. And the results showed that the leadership style of motivation, reward and punishment on loyalty with job satisfaction as an intervening variable. This study proves that job satisfaction acts as an intervening variable that relates the influence of leadership style, motivation, reward and punishment has a significant effect on loyalty. reward and punishment have a significant effect on loyalty, and the results of the study show that leadership style, motivation, reward and punishment, and job satisfaction have a significant effect on loyalty. And the results showed that the leadership style of motivation, reward and punishment on loyalty with job satisfaction as an intervening variable. This study proves that job satisfaction acts as an intervening variable that links the influence of leadership style, motivation, reward and punishment significantly on loyalty. reward and punishment have a significant effect on loyalty, and the results of the study show that leadership style, motivation, reward and punishment, and job satisfaction have a significant effect on loyalty. And the results showed that the leadership style of motivation, reward and punishment on loyalty with job satisfaction as an intervening variable. This study proves that job satisfaction acts as an intervening variable that relates the influence of leadership style, motivation, reward and punishment has a significant effect on loyalty. And the results showed that the leadership style of motivation, reward and punishment on loyalty with job satisfaction as an intervening variable. This study proves that job satisfaction acts as an intervening variable that relates the influence of leadership style, motivation, reward and punishment has a significant effect on loyalty. And the results showed that the leadership style of motivation, reward and punishment on loyalty with job satisfaction as an intervening variable. This study proves that job satisfaction acts as an intervening variable that relates the influence of leadership style, motivation, reward and punishment has a significant effect on loyalty